2022
DOI: 10.3390/cancers14225637
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Multiple Myeloma Is Reduced in Metformin Initiators: A Retrospective Cohort Study in Taiwanese Patients with Type 2 Diabetes Mellitus

Abstract: Background: Whether metformin might reduce the risk of multiple myeloma (MM) has not been extensively researched in humans. Methods: The study subjects were enrolled from the reimbursement database of Taiwan’s National Health Insurance. A total of 739,553 patients who had a new diagnosis of type 2 diabetes mellitus during 1999–2009 were identified. They were categorized as metformin initiators (metformin (+)) and non-metformin initiators (metformin (−)) based on the prescriptions of antidiabetic drugs that inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…Finally, 11 studies (18 effect sizes) with a total sample size of 2 318 217 participants and 6280 HCs cases, published between 2010 and 2023, were eligible ( Figure 1 ). 4 , 5 , 8 , 19 , 20 , 29 34 Some studies reported multiple effect sizes derived from their stratified analysis based on type of cancer or the gender of participants; we extracted all appropriate effect sizes to perform the meta-analyses. Nine of the articles were retrospective or prospective cohort studies; 5 , 19 , 20 , 29 , 30 , 32 34 two were nested case-control studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, 11 studies (18 effect sizes) with a total sample size of 2 318 217 participants and 6280 HCs cases, published between 2010 and 2023, were eligible ( Figure 1 ). 4 , 5 , 8 , 19 , 20 , 29 34 Some studies reported multiple effect sizes derived from their stratified analysis based on type of cancer or the gender of participants; we extracted all appropriate effect sizes to perform the meta-analyses. Nine of the articles were retrospective or prospective cohort studies; 5 , 19 , 20 , 29 , 30 , 32 34 two were nested case-control studies.…”
Section: Resultsmentioning
confidence: 99%
“… 17 , 18 Despite the promising results observed in preclinical studies, the association between metformin use and the risk of HCs in humans remains unclear; several observational studies have investigated this relationship, with conflicting results. 19 , 20 These studies have been limited by small sample sizes, the potential for confounding factors, and variability in the characteristics of the populations studied. Our analysis were performed to synthesize the available evidence from observational studies to provide more robust estimates of the association of metformin use in patients T2DM with the risk of HCs.…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33] A study has also revealed that type II diabetes patients who received metformin treatment have an obviously lower risk of MM. 34 Chidamide is a new oral benzamide-type selective HDAC inhibitor with anticancer activity in multiple cancers, such as hematologic cancer, lung carcinoma, and laryngeal carcinoma. [35][36][37] The HDAC inhibition and anticancer effects of chidamide have also been identified in MM development.…”
Section: Discussionmentioning
confidence: 99%
“…Metformin shows anticancer activities in various malignancies, including colorectal cancer, thyroid cancer along with head and neck cancer 31–33 . A study has also revealed that type II diabetes patients who received metformin treatment have an obviously lower risk of MM 34 . Chidamide is a new oral benzamide‐type selective HDAC inhibitor with anticancer activity in multiple cancers, such as hematologic cancer, lung carcinoma, and laryngeal carcinoma 35–37 .…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, a cohort of US veterans with comorbid MGUS and diabetes mellitus (DM) treated with metformin displayed reduction in myeloma risk with metformin exposure >4 years (21). Similarly, in a recently study of 739,553 patients from Taiwan's National Health Insurance database, T2DM patients who were prescribed metformin within the first year of their diagnosis with T2DM had a lower risk of developing MM compared to T2DM patients who were not prescribed metformin (42).…”
Section: Treatment Options For Targeting Obesity-related Contribution...mentioning
confidence: 99%